FRAUD HEPTAGON FACTORS AND FINANCIAL STATEMENT FRAUD: EMPIRICAL EVIDENCE FROM CONSUMER CYCLICALS FIRMS - Mohamad Zulman Hakim; Diva Septy Annisa; Rara Andini; Selvy Aprilianty (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2026)
This study examines the effect of the Fraud Heptagon elements on Financial Statement Fraud in Consumer Cyclicals sector companies listed on the Indonesia Stock Exchange during 2021–2024. Using the purposive sampling method, 29 companies were selected, resulting in 116 panel data observatiotions analyzed through panel data regression. The result show that Financial Target (ROA) negatively affects financial statement fraud, while External Pressure (LEVERAGE) and Change in Director (CID) have positive effects. In contrast, Financial Stability (ACHANGE), Personal Financial Need (OSHIP), Greed, Ideal Conditions of the Company (NOI), and Frequent Number of CEO Pictures (CEOPIC) show no significants effect. Ignorance and Effective Monitoring (BDOUT) negatively affect fraud, indicating that awareness and good supervision reduce manipulations risks. Meanwhile, Change in Auditor (CHAUD) positively influence fraud, suggesting that auditor changes may create opportunities for misconduct. Overall, the findings highlight that not all Fraud Heptagon elements significantsly affect financial statement fraud. However, governance quality, leadership stability, and external oversight remain crucial in preventing fraudulent financial reporting.